(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In the article, in order to increase the work efficiency of the temporary ditch digger, disk blades and a reel are installed on the front part of the dumper in order to soften the soil, reduce its resistance, improve the quality of the soil fraction and slope, and reduce water absorption and the results of theoretical research on determining the diameter of the reel, the coverage width, and the vertical load applied to the reel are presented.